2021
DOI: 10.1002/jmv.27486
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 antibody kinetics in blood donors with a previously positive SARS‐CoV‐2 antibody test within a seroprevalence survey

Abstract: The persistence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies is a matter of importance regarding the coronavirus disease 19 pandemic. To observe antibody dynamics, 105 blood donors, positive for SARS-CoV-2 antibodies by a lateral flow test within a seroprevalence study, were included in this study. Thirty-nine (37%) of 105 the donors were confirmed positive by a total Ig Wantai enzyme-linked immunosorbent assay (ELISA). Three (8%) in this group of 39 reported severe and 26/39 (67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Therefore, IgA is a good surrogate marker to predict the clinical course of COVID-19. In addition, a previous study reported that early baseline antibody levels were key drivers of the subsequent antibody production and the long-lasting protection against SARS-CoV-2 [ 48 50 ]. In accordance with the previous studies [ 48 , 49 ], we found that the level of anti-S1 IgA in COVID-19 patients was relatively high and was maintained over 9 months after infection (in over 70% and 80% of patients without pneumonia and with pneumonia, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IgA is a good surrogate marker to predict the clinical course of COVID-19. In addition, a previous study reported that early baseline antibody levels were key drivers of the subsequent antibody production and the long-lasting protection against SARS-CoV-2 [ 48 50 ]. In accordance with the previous studies [ 48 , 49 ], we found that the level of anti-S1 IgA in COVID-19 patients was relatively high and was maintained over 9 months after infection (in over 70% and 80% of patients without pneumonia and with pneumonia, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Participants gave their written informed consent to take part in the study. Between May 11, 2020, and May 24, 2022, 320 participants aged 14-87 years (median 31, IQR [25][26][27][28][29][30][31][32][33][34][35][36][37]) were recruited and followed for up to 837 days (median 155, IQR [58-277]). Two individuals lacked age information: 245 were males and 75 were females.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Multiple viral proteins (29,30) elicit prompt and longlasting immunity that persists for several months (31)(32)(33). SARS-CoV-2-directed S-and N-IgG, -IgM, and -IgA antibody profiles have guided inference of the serological response to COVID-19 and provided insight into the relevance of targeting the Spike-protein for vaccine design (34,35). Using data from European cohorts, mathematical modellers predicted the persistence of functional Spike and RBDdirected antibodies 465 days post-infection and faster decay of Ndirected antibodies, providing data that inform vaccination and serosurveillance strategies (36).…”
Section: Introductionmentioning
confidence: 99%